Selinunt, Italien. Forschungen in Selinunt, Teil 2. Die Arbeiten der Jahre 2020 und 2021 - Dally, Ortwin; Albers, Jon; Helas, Sophie; Miß, Axel; Schlöffel, Marlen; Schneider, Steffen (e-Forschungsberichte des DAI, 2022)
In 20220/21, work at Selinunte could continue despite the pandemic. Apart from a new DFG project on the diachronic development of the city (see Jonasch et al. 2022), work on the design of the sacred space on the agora and in the eastern harbour of Selinunte could be brought forward. In addition, there were drill-cored landscape archaeological investigations.